undernet wrote:

\(\frac{p+5+p^3(-p-5)}{-p-5}=\)

A. p+5+p^3

B. P^3+5

C. p^3

D. p^3-1

E. p^3-5

We're looking for an expression that is

equivalent to the original expression.

So if we evaluate the original expression for a particular value of p, then the equivalent expression should also yield the same value when we plug in the same value of p.

Let's test p =

1Take: [p + 5 + p³(-p - 5)]/[-p - 5]

Replace p with

1 to get: [

1 + 5 +

1³(-

1 - 5)]/[-

1 - 5]

Evaluate to get: 0/-6, which equals

0So, when p =

1, the original express evaluates to be

0 Now let's plug p =

1 into the answer choices....

A.

1 + 5 +

1^3 =

7. No good, we want

0. ELIMINATE.

B.

1^3 + 5 =

6. No good, we want

0. ELIMINATE.

C.

1^3 =

1. No good, we want

0. ELIMINATE.

D.

1^3 - 1 =

0. Great - KEEP

E.

1^3 - 5 =

-4. No good, we want

0. ELIMINATE.

Answer: D

Cheers,

Brent

_________________

Brent Hanneson – Founder of gmatprepnow.com